Бельчонок Тишка: [для детей дошкольного возраста / И. В. Гурина] - Гурина Ирина Валерьевна (Фламинго, 2016)
Экземпляры: Ф22 (20161123) / Инвентарный номер: 53137 / Цена: 31.00 / Сис.шифр: Д / Авт.знак: Г 95 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6